Identification and molecular detection of Arbuscular Mycorrhizal Fungi colonized naturally in citrus roots in nurseries - YENNY SARIASIH; SITI SUBANDIYAH; SRI WIDYANINGSIH; TAHIR KHURSHID; JIANHUA MO (Society for Indonesian Biodiversity, 2023)
Abstract. Sariasih Y, Subandiyah S, Widyaningsih S, Khurshid T, Mo J. 2023. Identification and molecular detection of Arbuscular Mycorrhizal Fungi colonized naturally in citrus roots in nurseries. Biodiversitas 24: 6283-6290. Citrus plants heavily depend on arbuscular mycorrhizal (AMF), a diverse collection of fungi. The objective of this study was to investigate the root colonization, spore density, spore morphology, and molecular identification of AMF colonizing four citrus root species: Japansche Citroen (Citrus limonia Osbeck.), Cleopatra mandarin (Citrus reshni), Salam (Fortunella japonica cv.